Inside Cover: Templated Atom‐Precise Galvanic Synthesis and Structure Elucidation of a [Ag24Au(SR)18]− Nanocluster (Angew. Chem. Int. Ed. 3/2016). Issue 3 (14th December 2015) - Bootharaju, Megalamane S.; Joshi, Chakra P.; Parida, Manas R.; Mohammed, Omar F.; Bakr, Osman M.
Abstract : The synthesis of atom‐precise alloy nanoclusters with uniform composition is challenging when the atoms forming the alloy have similar size. In their Communication onpage 922 ff., O. M. Bakr et al. describe how they tackled the selective replacement of the central silver atom of [Ag25 (SR)18 ] − with one gold atom by a galvanic exchange strategy. The enhanced optical properties and stability of [Ag24 Au(SR)18 ] − allowed properties to be compared at the single‐atom level.